Padel Sebagai Bisnis Dan Arena Konsumsi Simbolik: Analisis Nilai Tanda Dalam Pembentukan Gaya Hidup - Zahra Putri Fadhilah; Subhan Widiansyah (Jurnal Sosiologi Nusantara, 2026)
The popularity of padel in Indonesia has continued to rise in recent years. This growth has coincided with the expansion of social media as a space that shapes the image and social meaning of padel. The study aims to explain the process of producing symbolic value in padel and how this value is consumed in shaping players’ lifestyles. It employs a qualitative method with a phenomenological approach to analyze players’ experiences and subjective interpretations of padel activities. The study involved five informants selected through purposive sampling, consisting of individuals involved in padel promotion, tournament organizers, and beginner players. Data were collected through in-depth interviews, observation, and documentation. The findings indicate that symbolic value in padel is not produced individually but is shaped through collaboration between brands, communities, and social media. Social media functions not only as a communication tool but also as a space for the production and dissemination of meaning that drives symbolic consumption, where players engage in padel not for its functional purpose but for the social meanings attached to it. This symbolic consumption develops into a lifestyle, reflected in the documentation of playing activities and the use of leisure time. This finding extends the application of Jean Baudrillard’s theory of consumption to the context of sport by demonstrating that padel is not only consumed as a sporting activity but also as a symbol of identity and social recognition, which is reproduced as part of players’ lifestyle.